2007
DOI: 10.1002/maco.200704087
|View full text |Cite
|
Sign up to set email alerts
|

The factor time at the formation and development of the passive layer in the atmosphere

Abstract: Passive layers on high alloyed chromium nickel steels protect the metal from corrosion. The protective effect of the passive layer, however, does not immediately exist after the final surface treatment. Some time is necessary to form the protective layer. The exposure conditions are also decisive for the formation and further development of the passive layer besides the surface treatment. Samples of different chromium nickel steels are pickled and active passivated before they are exposed under laboratory cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Excluding additional passivation treatments, a certain time under atmospheric conditions is necessary for the stabilization of the passive film. Bierwirth, et al, [18][19] confirmed, by means of EN measurements carried out in 1 M NaCl solution at pH 3, that the protective effect of the passive layer formed on mechanically ground surfaces of Type 316 (UNS S31600) stainless steel depends strongly on the atmospheric conditions and the corresponding aging time. A passive layer aged at 50% of relative humidity stabilizes considerably slower than those aged at a relative humidity higher than 90%.…”
Section: -2mentioning
confidence: 59%
See 2 more Smart Citations
“…Excluding additional passivation treatments, a certain time under atmospheric conditions is necessary for the stabilization of the passive film. Bierwirth, et al, [18][19] confirmed, by means of EN measurements carried out in 1 M NaCl solution at pH 3, that the protective effect of the passive layer formed on mechanically ground surfaces of Type 316 (UNS S31600) stainless steel depends strongly on the atmospheric conditions and the corresponding aging time. A passive layer aged at 50% of relative humidity stabilizes considerably slower than those aged at a relative humidity higher than 90%.…”
Section: -2mentioning
confidence: 59%
“…7 Preliminary surface treatments have not only a direct bearing on the surface appearance but also play a decisive role for future corrosion protectiveness of the stainless steel surface. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Burstein and coworkers [8][9] pointed out, for instance, that the susceptibility of stainless steels to pitting corrosion in chloridecontaining solutions is affected significantly by the surface finish. According to the authors, transition from metastable pitting to stable pitting corrosion is affected by surface roughness because pit growth is controlled by the diffusion rate, which is governed by the pit geometry controlling the electrolyte composition into the pit.…”
Section: -2mentioning
confidence: 99%
See 1 more Smart Citation
“…The typically applied surface treatments, such as grinding, polishing and blasting will not only determine the appearance and mechanical properties of stainless steel surfaces but also have an impact on the corrosion resistance [12]. For example, homogeneous surfaces with low roughness exhibit faster and more stable passive film formation with higher corrosion protection compared to rough surfaces under the same conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other major influencing factors affecting the corrosion behavior are the surface treatment and relative humidity in the time before any corrosion investigation, which can have positive and negative effects . Tempering colors formed due to high mechanical load during surface treatment have a significant negative influence on passive film formation.…”
Section: Introductionmentioning
confidence: 99%